A supramolecular fluorescent vesicle based on a coordinating aggregation induced emission amphiphile: insight into the role of electrical charge in cancer cell division. Issue 84 (3rd October 2016) - Li, Jie; Shi, Kangjie; Drechsler, Markus; Tang, Ben Zhong; Huang, Jianbin; Yan, Yun
Abstract : Coordination of Zn 2+ triggers increased electrical charge of a fluorescent vesicle which further drives fission of the vesicle. Abstract : Binding of Zn 2+ to the coordinating supramolecular vesicle based on an aggregation induced emission amphiphile TPE-BPA immediately triggers the formation of charged vesicles. This induces vesicle fission and fluorescence reduction, suggesting a looser molecular packing in the charged vesicle membrane. Since cancer cells are highly charged, this indicates that the quick fission of cancer cells may have electrical charge origin.